Contemporary issues in Caribbean and Latin American relations - Kirton, R. Mark (Raymond Mark), 1951-; Anatol, Marlon (Lexington Books, 2021)
"This publication addresses several contemporary issues impacting the relations between the Caribbean and Latin America including challenges relation to migration, security, economic and political integration, in the context of the current global environment. Against this background, the publication also seeks to provide recommendations and options"--